TRAINING ON THE USE OF EDUPOINT: MINI DRIVE LEARNING RESOURCES FOR DISASTER EMERGENCY SCHOOLS IN PADALUYU VILLAGE, CUGENANG SUB-DISTRICT, CIANJUR REGENCY - Supriadi, Dedi; Muhyidin Nurzaelani, Mohammad; Yuda Pratama, Erik; Ibnu Anwar, Thoriq; Asidiqi, Khudri (LPPM Univ. Ibn Khaldun Bogor, 2023)
The results of initial observations, especially in Padaluyu Village, Cugenang District, obtained data that there were 27 RTs spread across Padaluyu Village. The condition of 8 RTs experienced very severe damage (all houses collapsed) 19 RTs experienced severe and moderate damage. There are elementary schools in Cugenang District that need assistance related to the implementation of learning, especially the availability of learning resources, namely SDN Padamamur, SDN Padaluyu, and SDN Kembang Manis 2. The purpose of implementing this PKM is to overcome problems experienced by partners related to obstacles in the learning process that occur due to the earthquake. With the damage to some school rooms, learning must be diverted elsewhere. Therefore the development of Edupoint is considered appropriate to overcome this problem. EduPoint is a learning tool designed as a medium for providing access to mobile learning that can be accessed via various devices such as laptops, computers, smartphones and tablets in a local network so that it does not require quota or unstable signals due to earthquake conditions. This tool is designed so that students can study anywhere without having to take place in the classroom. The design concept of this tool is intended to accommodate the learning process so that it can continue under any conditions so that it can be easily moved wherever learning conditions take place (portable). After completing the development of the tool, training is needed for teachers to use it. The training activity on using EduPoint: Mini Drive Learning Resources for Disaster Emergency Schools ran smoothly. The response from the partners and training participants was very good thanks to the good cooperation between the University of Ibn Khaldun Bogor and the partners involved. The results of the training show that teachers are able to properly use the learning resources accessed through EduPoint.